Chlorophyll-a Outliers in the Banda Sea and its surroundings: Implications for Ecosystem Dynamics - Asuhadi, Sunarwan; Zainuddin, Mukti; Safruddin, Safruddin; Musbir, Musbir; Syah, Achmad Fachruddin (Marine Science Department Diponegoro University, 2024)
Chlorophyll-a concentration is a critical indicator of marine ecosystem health, reflecting primary productivity and potential ecological changes. However, the occurrence of outlier data in the Banda Sea and its surroundings has not been sufficiently studied. This study aims to investigate the dynamics of chlorophyll-a concentration outliers in the Banda Sea, focusing on their spatial and temporal patterns from 2010 to 2022. Data were acquired from MODIS satellite imagery and analyzed using R Studio for time series decomposition, while spatial patterns were explored with ArcGIS 10.8 and Google Maps to pinpoint key hotspots of outlier activity. The findings reveal fluctuating chlorophyll-a outliers with extreme concentrations ranging from 14.39 to 81 mg·m⁻³. Temporally, these outliers are predominantly observed in the western Banda Sea during January to March and December, while in the eastern Banda Sea they occur from June to September. Spatially, these anomalies are concentrated in areas of significant human activity, particularly in Tolo Bay, suggesting a potential link between anthropogenic influences and ecological disruptions. Field monitoring in areas with persistent outliers is strongly recommended to verify actual conditions and assess their ecological impacts. While chlorophyll-a plays a vital role in marine productivity, excessive concentrations can disrupt ecosystems, potentially leading to harmful algal blooms or hypoxic conditions. This study underscores the importance of integrating remote sensing, field validation, and spatial analysis to effectively monitor and manage these anomalies. Enhanced understanding of these dynamics is critical for informed decision-making and sustainable marine management practices in the Banda Sea.